Transforming Labour: Women and Work in Post-War Canada - Sangster, Joan (University of Toronto Press, 2010)
The increased participation of women in the labour force was one of the most significant changes to Canadian social life during the quarter century after the close of the Second World War. Transforming Labour offers one of the first critical assessments of women's paid labour in this era, a period when more and more women, particularly those with families, were going 'out to work'. Using case studies from across Canada, Joan Sangster explores a range of themes, including women's experiences within unions, Aboriginal women's changing patterns of work, and the challenges faced by immigrant women. By charting women's own efforts to ameliorate their work lives as well as factors that re-shaped the labour force, Sangster challenges the commonplace perception of this era as one of conformity, domesticity for women, and feminist inactivity. Working women's collective grievances fuelled their desire for change, culminating in challenges to the status quo in the 1960s, when they voiced their discontent, calling for a new world of work and better opportunities for themselves and their daughters. –Publisher's description
https://utorontopress.com/us/transforming-labour-4
Keywords: Employment; History; Labor Unions; Social conditions; Women